Brozopine Inhibits 15-LOX-2 Metabolism Pathway After Transient Focal Cerebral Ischemia in Rats and OGD/R-Induced Hypoxia Injury in PC12 Cells - Gao, Yuan; Cao, Xinyu; Zhang, Xiaojiao; Wang, Yangjun; Huang, He; Meng, Yonggang; Chang, Junbiao (Frontiers in Pharmacology, 2020)
The goal of this study was to elucidate the mechanisms of protection of Sodium (±)-5-bromo-2-(α-hydroxypentyl) benzoate (trade name: Brozopine, BZP) against cerebral ischemia in vivo and in vitro. To explore the protective effect of BZP on focal cerebral ischemia-reperfusion injury, we evaluated the effects of various doses of BZP on neurobehavioral score, cerebral infarction volume, cerebral swelling in MCAO rats (ischemia for 2h, reperfusion for 24h). In addition, the effects of various doses of BZP on OGD/R-induced-PC12 cells injury (hypoglycemic medium containing 30 mmol Na2S2O4 for 2h, reoxygenation for 24h) were evaluated. Four in vivo and in vitro groups were evaluated to characterize targets of BZP: Control group, Model group, BZP group (10mg/kg)/BZP group (30μmol/L), C8E4 group (10mg/kg)/C8E4 group (30μmol/L). An ELISA kit was used to determine the levels of 15-HETE (a 15-LOX-2 metabolite) in vivo and in vitro. Rat nuclear factor κB subunit p65 (NF-κB p65), tumor necrosis factor (TNF-α), interleukin-6 (IL-6), and intercellular adhesion molecule-1 (ICAM-1) were also quantified in vivo and in vitro. The results showed that BZP improved focal cerebral ischemia-reperfusion injury in rats and PC12 cells treated with Na2S2O4 in dose/concentration-dependent manners through inhibition of production of 15-HETE and expression of NF-κB, IL-6, TNF-α, and ICAM-1. In conclusion, BZP exerted protective effects against cerebral ischemia via inhibition of 15-LOX-2 activity.